1999
DOI: 10.1053/tvjl.1998.0303
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis

Abstract: Vesicular stomatitis is a disease of livestock caused by some members of the Vesiculovirus genus (Family Rhabdoviridae), two of which are called 'vesicular stomatitis virus'. Clinical disease presents as severe vesiculation and/or ulceration of the tongue, oral tissues, feet, and teats, and results in substantial loss of productivity. Except for its appearance in horses, it is clinically indistinguishable from foot-and-mouth disease. Unlike foot-and-mouth disease, it is very infectious for man and can cause a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
259
1
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(272 citation statements)
references
References 0 publications
4
259
1
8
Order By: Relevance
“…The apparent incubation time of VSV in opossums experimentally infected through the routes used in this study was 48 hr, which is similar to the time described for cattle experimentally infected with VSNJV and VSIV (Mason, 1978;Yuill, 1981;Arbelá ez and Rocha, 1984;Letchworth et al, 1999;Schmitt, 2002). The clinical signs, and the extension and kinetics of lesions observed in experimentally infected opossums, were similar to the ones described for bovine, equine, and porcine subjects when these were experimentally inoculated (Howerth et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The apparent incubation time of VSV in opossums experimentally infected through the routes used in this study was 48 hr, which is similar to the time described for cattle experimentally infected with VSNJV and VSIV (Mason, 1978;Yuill, 1981;Arbelá ez and Rocha, 1984;Letchworth et al, 1999;Schmitt, 2002). The clinical signs, and the extension and kinetics of lesions observed in experimentally infected opossums, were similar to the ones described for bovine, equine, and porcine subjects when these were experimentally inoculated (Howerth et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…This disease primarily affects domestic cattle, horses, and swine, but also has been observed infrequently in camelids, sheep, goats, and some wildlife species; humans can also become infected, producing an acute, febrile, influenza-like illness (Thorne et al, 1983;Letchworth et al, 1999;McCluskey and Mumford, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, almost 50% of horses in an outbreak are affected. 11,12 Stomatitis was also reported as one of several clinical findings in an outbreak of EVA in Spain 14 ; but the seronegative status of the horse herd made this an unlikely cause in the present case. Jamestown Canyon virus, an isolate of California encephalitis virus, was isolated from vesicular lesions from the coronary band, tongue, and buccal mucosa from a horse that presented with anorexia and weight loss.…”
mentioning
confidence: 64%
“…27 Vesicular stomatitis virus ͑VSV͒ is an ssRNA virus that is vector-transmitted by some insects and causes disease in certain mammal species. 28,29 Two diverged populations of VSV were characterized for reproductive growth on tissue culture cells, and for within-population variance among clones for this phenotype; this effort revealed that one population was slow-growing but relatively less variable in clone phenotypes ͑robust͒ and the other had the opposite characteristics ͑brittle͒. 27 Whereas standard growth conditions allowed the faster replicating brittle virus population to outcompete the slower replicating robust population, exposure to either of two mutagens favored the robust variant.…”
Section: Empirical Evidence For Evolution Of Robustness In Rna VImentioning
confidence: 99%